Drug use in Ghana: knowledge, perceptions, and attitudes in a small group of elite student sportspersons - Brown Ato A.; Asare Pereko Kingsley K.; Eliason Sebastian (Sciendo, 2013)
Study aim: This study assessed the level of knowledge, perceptions, and attitudes of tertiary student athletes on doping issues. Emphasis was placed on the knowledge of substances found on the prohibited list of the World Anti- Doping Agency (WADA) as well as the potential effects and side effects of the drugs when consumed.